if $M$ is the midpoint of $BC$ then find the measure of $AMC$.

enter image description here

I tried to use the angles to find $AMC$ but I don't know how to use that $M$ is the midpoint of $BC$.


The answer is $\color{red}{45^\circ}$. You may embed the construction in the complex plane by assuming $C=1, B=-1$. Then $A$ has to fulfill: $$A-C = \lambda e^{5\pi i/6},\qquad A-B = \mu e^{\pi i/12},\qquad (\lambda,\mu\in\mathbb{R}) $$ but that leads to $A=\eta(1+i)$, and the claim follows.

An alternative, elementary way. By assuming $BM=MC=1$ we have: $$ AC = 2\frac{\sin 15^\circ}{\sin 135^\circ}=-1+\sqrt{3},\qquad AB = 2\frac{\sin 30^\circ}{\sin 135^\circ}=\sqrt{2}$$ by the sine theorem. By Stewart's theorem we have: $$ AM^2 = \frac{2AB^2+2AC^2-BC^2}{4} = \left(\frac{\sqrt{3}-1}{\sqrt{2}}\right)^2$$ and by the sine theorem again: $$ \sin\widehat{CMA} = AC\cdot\frac{\sin 30^\circ}{AM} = \frac{1}{\sqrt{2}},$$ from which $\widehat{CMA}=\color{red}{45^\circ}$.

  • $\begingroup$ How can you directly conclude that $A=\eta(1+i)$ $\endgroup$ – Hamza Jun 9 '16 at 17:28
  • $\begingroup$ You have to make some computation, but that is an easy task. $\endgroup$ – Jack D'Aurizio Jun 9 '16 at 17:31
  • $\begingroup$ But isn't it better to use geometry to solve a geometry question? Analytical methods seem non intuitive $\endgroup$ – N.S.JOHN Aug 14 '16 at 12:40

I asked this from our teacher and he give this answer may helps also this answer don't uses trigonometry:

enter image description here

$BNC=90$degrees and $BAN=45$ then we have $AN=BN$ also because $BNC$ is right angle $MN=BM$ also because $NBM=60$,the triangle $BNM$ is equilateral.Also $MNA=30$ then because $MN=AN$ the angle $NMA=75$ then we have $AMC=45$.

  • $\begingroup$ What is your question? You want to know why the angle is 45°? (do you want a proof... do you want more explanation on the proof provided by your teacher?) Or...? $\endgroup$ – Omid Ghayour Jun 10 '16 at 17:58
  • $\begingroup$ No I just added an answer. $\endgroup$ – Taha Akbari Jun 11 '16 at 5:30
  • $\begingroup$ add answer to which quesstion!? the asker's name and the answerer's name are same... ☺ $\endgroup$ – Omid Ghayour Jun 11 '16 at 7:22
  • $\begingroup$ Ok I first asked the question before then tommorow our teacher give this answer I put it because I think it is usuful $\endgroup$ – Taha Akbari Jun 11 '16 at 7:36
  • $\begingroup$ OK!... then... I wrote a fully explained... but short... without talking about unnecessary facts... $\endgroup$ – Omid Ghayour Jun 11 '16 at 12:07

Let $X$ be the point on $BC$ exactly below $A$ and $MX=z$ for comfort.

$BX=\frac{BC}{2}+z$ and $XC=\frac{BC}{2}-z$


$$\tan(\alpha )= \frac{AX}{BX}\implies \tan(\alpha )= \frac{AX}{\frac{BC}{2}+z}$$

$$\tan(AMC )= \frac{AX}{Z}$$

$$\tan(\beta )= \frac{AX}{XC} \implies \tan(\beta )= \frac{AX}{\frac{BC}{2}-z}$$

Now you have 3 questions with 3 variables $z,AX,\tan(AMC)$ and the rest is given. Let $AMC= \gamma$

$$AX=z \tan(\gamma)$$

$$(1)\tan(\alpha )= \frac{z \tan(\gamma)}{\frac{BC}{2}+z}\implies \frac{BC\tan(\alpha )}{2}=z(\tan(\gamma)-\tan(\alpha ))$$

$$(2)\tan(\beta )= \frac{z \tan(\gamma)}{\frac{BC}{2}+z}\implies \frac{BC\tan(\beta )}{2}=z(\tan(\gamma)+\tan(\beta ))$$

And by dividing (1)/(2) we get:

$$\frac{\tan(\alpha )}{\tan(\beta )}=\frac{\tan(\gamma)-\tan(\alpha )}{\tan(\gamma)+\tan(\beta )}$$

Hence: $$\tan(\gamma)=\frac{2\tan(\alpha)\tan(\beta)}{\tan(\beta)-\tan(\alpha)}$$


  • $\begingroup$ now whats the answer? $\endgroup$ – Taha Akbari Jun 9 '16 at 14:37
  • $\begingroup$ I think I can safely let you proceed.. You have $\alpha$ and $\beta$. All you need is a calculator. $\endgroup$ – havakok Jun 9 '16 at 14:57

enter image description here Continue $CA$, draw the ray $\vec{CA}$. Then draw $BN$, in which it is perpendicular to $\vec{CA}$.

$\triangle BCN$ is a 30-60-90 triangle. as we know about this triangle. $BN=\frac12 BC$. So $BN=BM$. This tells us $\triangle ABN$, is isosceles, so $\angle BMN=\angle BNM=\frac{180^\circ-\angle MBN}2=\frac{120^\circ}{2}=60^\circ$.

  • Now we know $\triangle BMN$ is equilateral.

Therefor $$MN=BN=BM\qquad(1)\\ \text{and }\angle MBN=60^\circ\qquad{ }$$

By this, we get $\angle CMN=180^\circ-\angle BMN=180^\circ-60^\circ$, $$\text{therefor }\angle CMN=120^\circ\ (2)$$

$\angle ABN=\angle CBN-\angle CBA=60^\circ-15^\circ=45^\circ$. So, the other angle of the right triangle $\triangle ABN$, i.e. $\angle BAN$, should be $180^\circ-90^\circ-45^\circ=45^\circ{}^\dagger$, therefor $\triangle ABN$ is isosceles.

So we would have $AN=BN$. By (1) we get $MN=AN$, so $\triangle AMN$ is isosceles. Therefor $$\angle AMN=\angle MAN=\frac{180^\circ-\angle ANM}2=\frac{180^\circ-30^\circ}2=75^\circ$$

Now, by using (2) we can find the size of $\angle AMC$, which is $$\angle AMC=\angle CMN-\angle AMN=120^\circ-75^\circ=45^\circ$$

${}^\dagger$let's note that one may also know that $\angle BAN$ is equal to $45^\circ$, since it is an external angle of the triangle $\triangle ABC$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.